Morphological features and molecular mechanisms in peritoneal adhesions from patients with chronic abdominal postoperative painResearch in context - Masja Karina Toneman; Priscilla Pauline Marianne Faas; Maurits Johan Christian Antoine Marie Gielen; Valentina Carotti; Anne Elisa Adriana van Oirschot; Judith Petronella Maria Mangnus; Anne Wintjens; Casper Mihl; Josephine Huige; Bianca Grosser; Marjolein Blussé van Oud-Alblas; Koen Willem van Dongen; et al. (EBioMedicine)
Summary: Background: Chronic abdominal pain affects 10–20% of all patients following abdominal surgery, with adhesions as a predominant cause. However, the biological mechanisms underlying adhesion-related pain are not fully elucidated. This study aimed to establish the morphological and molecular phenotype of adhesions in patients with and without chronic postoperative abdominal pain. Methods: In this case–control study, biopsies of adhesions were obtained from patients with chronic postoperative abdominal pain (related to adhesions on cineMRI) and controls without pain, from two tertiary care and one secondary care hospital. Quantitative histological analysis of haematoxylin and eosin-stained sections was performed, while immunohistochemical (IHC) markers for nerve tissue (S100, calretinin and synaptophysin) were quantified through image analysis. RNA expression of genes (TRPV1, BDNF, TAC1, TACR1, NGF) was measured using real time quantitative polymerase chain reaction (RT-qPCR). Controls were matched to cases by sex, age, and prior surgery, accepting small variations due to patient availability. An independent two-sided t-test was used to detect differences in IHC and RT-qPCR analysis between groups. Findings: Adhesions from 31 patients with pain were compared to those from 31 patients without pain, consisting of 48% connective tissue and 41% adipose tissue. Immunohistochemical analysis revealed increased nerve tissue in patients with pain (S100: median 597 ppm (range 92.2–3223.2 ppm) vs 151 ppm (range 15.2–1683.8 ppm) p < 0.001; calretinin: median 463 ppm (range 72.7–2996.5 ppm) vs 275 ppm (range 35.3–3194.8 ppm) p = 0.040). NGF showed a higher mRNA expression in adhesions from patients with pain compared to controls (p = 0.012). Interpretation: This study suggests a distinct morphological and molecular phenotype of adhesions in patients experiencing adhesion-related pain, providing insights into underlying mechanisms. Funding: Veni grant from The Dutch Governmental Organisation for Health Research and Development (ZonMw grant number 91619035).